Stimulus Pemasaran Produk Kopi terhadap Kepuasan dan Loyalitas Konsumen - Indra Hartini (IPM2KPE, 2021)
This study aimed to determine the effect of marketing stimulus on consumer satisfaction, the effect of marketing stimulus on consumer loyalty, and the effect of marketing stimulus on consumer loyalty through the consumer satisfaction of Tanah Puyang Coffee Shop in Lahat City. This research method is descriptive analysis method and statistical analysis. The number of samples was determined using quota sampling as many as 110 customers of the Tanah Puyang Coffee Shop as respondents, while the determination of the sample was carried out using accidental sampling. Data was collected by conducting interviews based on a prepared questionnaire. Data were analyzed using path analysis. The results of the study, the value of sig in Path Analysis, namely, a) the price variable has a sig value of 0.023 < 0.05; b) The flavor variable has a sig value of 0.386 > 0.05; c) The service quality variable has a sig value of 0.00 < 0.05; d) The promotion variable has a sig value of 0.004 < 0.05. The service quality variable, promotion variable, and consumer satisfaction variable on consumer loyalty have a sig value. respectively, namely, 0.00 < 0.05, 0.005 < 0.05, 0.028 < 0.05. In conclusion, price, service quality, and promotion have an influence on consumer satisfaction. Service quality, promotion, and consumer satisfaction affect consumer loyalty. Service quality and promotion through customer satisfaction have an influence on consumer loyalty for Kedai Tanah Puyang coffee products. Keywords: Consumer Satisfaction, Consumer Loyalty, Marketing Stimulus